Exploring Artificial Intelligence Governance in the UK - ABIDI RACHID; BELKHIR MANAL (University of El-Oued جامعة الوادي, 2025)
This study discusses and explores the UK’s AI management frame, as formalized in the AI regulation White Paper 2023. It aims to unravel the effectiveness of this frame to cope with the rapidly changing technology, along with exploring the constraints that face its implementation in practice. To gain comprehensive findings, the study employs a qualitative approach in research. The data gathered is both primary – policy papers and official reports – and secondary – stakeholders’ views on the white paper and related scholarly works. A descriptive-thematic analysis id used in analyzing the white paper pro-innovation approach to highlight the main themes it focuses on. To evaluate the effectiveness of this approach and explore the constraints it faces, a secondary critical analysis, based on stakeholders’ lens and experts’ commentary, is used. This analysis is accompanied by a comparative analysis that compares the UK’s approach to others and case studies that evaluate the implementation of the approach in some sectors.The findings show both strengths and weaknesses of the UK’ approach. They investigate that the UK’s sectoral approach to AI governance is valuable in a global context. However, they demonstrate a gap betweenthe approach framework and its actual implementation, which causes public distrust. Demonstrated challengesinclude: inconsistency in transparency, regulatory ambiguity, expertise and funding deficits, and inadequate protections. Accordingly, it is recommended that anincreased regulatory adjustment and investment in regulatory capacity and detailed guidelines and risk assessments, with a focus on clear definitions and international alignment, are needed to address the regulatory gap.
Master's Degree In Literature and Civilization
Keywords: AI Governance; AI Regulation; Pro-innovation Approach; Regulatory Framework; Stakeholder.